Role of sonication time on thermal behaviour and dynamic mechanical analysis of NiZn ferrite incorporated PLA/LNR nanocomposite - Shahdan, Dalila; Flaifel, Moayad Husein; Chen, Ruey Shan; Ahmad, Sahrim; Hassan, Aziz (Indian Academy of Sciences, 2019)
The investigation on thermal properties of polylactic acid/liquid natural rubber (PLA/LNR) blend embedded with nickel zinc (NiZn) ferrite nanoparticles at various loading (1-5 wt%) and treated with different ultrasonication time (1-2 h) is the main core of this study. The novel NiZn nanocomposite based on the matrix of PLA:LNR with a ratio of 90:10 was fabricated via melt blending technique with the aids of ultrasonication. The effects of nanofiller loading and ultrasonic treatment on nanocomposite were examined by scanning electron microscopy, differential scanning calorimetry and dynamic mechanical analyser. The results revealed that the thermal properties of PLA/LNR matrix have improved with incorporation of nanoparticles in which improvement was observed until an optimum level at 4 wt% NiZn ferrite within 1 h of ultrasonic treatment. The optimum ultrasonication for 1 h is believed to be sufficient to promote a good dispersion of NiZn ferrite nanoparticles within the PLA/LNR and in order to enhance the thermal stability, which makes it potentially to be used in electronic applications. © Indian Academy of Sciences.